Marine micromorphology in 3D: Visualisation of a submerged midden site from Hjarnø, Denmark. (February 2019) - Ward, I.; Maksimenko, A.
Abstract: Micromorphology is traditionally done in two-dimensions from thin section. Here we use X-ray computed tomographic imaging to provide microspatial three-dimensional imaging of a section of a submerged shell midden from Denmark. The 3D imaging complements traditional micromorphological methods to provide greater interpretive power of the biogenic structure and taphonomy of the archaeological remains within the midden. Examples include the different degree of fracturing within shell layers, presence of epizootic infestation in several oyster shells and morphology of a flint artefact. Whilst higher-resolution micro-computed tomographic imaging would offer potential to better resolve micron-scale features, these preliminary results highlight the potential of X-ray tomography to resolve and document structural and morphological features of embedded archaeological materials without the need for invasive procedures. Highlights: Use of X-ray micro-computed tomography to provide 3D visualisation of a submerged shell midden Worm burrows in oyster shells provide support for the positioning of the midden at or below the shoreline. Demonstrated advantage of non-invasive X-ray CT imaging for cultural materials Added interpretative power of large area CT imaging to standard 2D micromorphology